Impact of mother's education on full immunization of children aged 12-23 months in Eritrea: population and health survey 2010 data analysis - Kibreab, F; Lewycka, S; Tewelde, A (BioMed Central, 2020)
Background Although vaccination coverage in Eritrea has improved in recent years, some children are still missing out, and it’s important to identify risk factors for lower coverage in order to target campaigns and interventions. The objective of this study was to assess: (1) the impact of maternal education on full immunization of children aged 12–23 months, and (2) whether the association was confounded or modified by other factors. Methods This study was a secondary data analysis of the Eritrean Population and Health Survey 2010 (EPHS 2010). In this analysis 1323 mothers of children aged 12–23 months were included. The outcome of the study was full immunization, defined as receiving all the WHO recommended basic vaccines: one dose of Bacillus Calmette-Gué rin (BCG), three doses of diphtheria-pertussis-tetanus(DPT), three doses of polio, and one dose of measles vaccine. The primary exposure was maternal education. Data on immunization coverage came from vaccination cards and from mothers’ or caretakers’ verbal reports. Bivariate and multivariable logistic regression analyses were performed. Result Full vaccination coverage among children aged 12–23 months was 83%. Most children received BCG (95%), DPT1 (97%), DPT2 (96%), DPT3 (93%), polio1 (97%), polio2 (97%), polio3 (91%) and measles (92%). In unadjusted analyses, children of mothers with primary (OR = 2.75, 95% CI 1.74–4.37), and middle or above (OR = 3.16, 95% CI 2.09–4.78) education were more likely to be fully immunised. However, after adjusting for wealth, region, ANC visit, and vaccination card ownership, only the effect for primary education remained significant (OR = 2.34, 95% CI 1.30–4.21). Conclusion The result of this study suggested that children of mothers who attained primary level were more likely to be fully vaccinated than children of mothers with no education. The association was influenced by wealth index of household, mothers ANC visit, region, and possession of vaccination card. The Expanded Program on Immunization of the Ministry of Health should target strategies to enhance full immunization among children of mothers with no education.